1999
DOI: 10.1037/0735-7036.113.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Social learning of an artificial fruit task in capuchin monkeys (Cebus apella).

Abstract: Social learning in 11 human-raised capuchin monkeys (Cebus apella) was investigated using an artificial fruit that was designed as an analogue of natural foraging problems faced by primates. Each subject observed a human model open each of 3 principal components on the fruit in 1 of 2 alternative ways ("morphs"). The capuchin monkeys reproduced, to differing extents, the alternative techniques used for opening 1 component of the task (poking vs. pulling while twisting out a pair of smooth plastic bolts) but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
149
0
9

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(161 citation statements)
references
References 56 publications
3
149
0
9
Order By: Relevance
“…This was despite the fact that other effective alternatives were available, such as pulling from the screw handles which had been intentionally placed on the apparatus for that purpose (see method section). In the study carried out by Custance et al (1999) with capuchin monkeys, they suggested that the idiosynchratic methods chosen by the subjects were suggestive of object-movement re-enactment (a form of emulation), rather than imitation. However, no such effect was found in the current study as monkeys in from the same demonstration groups were highly consistent in their preferred methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was despite the fact that other effective alternatives were available, such as pulling from the screw handles which had been intentionally placed on the apparatus for that purpose (see method section). In the study carried out by Custance et al (1999) with capuchin monkeys, they suggested that the idiosynchratic methods chosen by the subjects were suggestive of object-movement re-enactment (a form of emulation), rather than imitation. However, no such effect was found in the current study as monkeys in from the same demonstration groups were highly consistent in their preferred methods.…”
Section: Discussionmentioning
confidence: 99%
“…Whiten et al (1996), Custance et al (1999), and Voelkl and Huber (2000) all describe clearly in their methods sections the delay between demonstration and trials, and in each case, subjects were tested for only a matter of minutes following the demonstrations. The typically short duration of such studies has meant that we currently know little about how long socially learned behaviours will remain in primates' repertoires, especially once subjects have been given an opportunity to interact with the relevant objects themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Consider cases in which an observer reproduces the movements of objects caused by a model, a category that Custance, Whiten, and Fredman (1999) have described as "object movement re-enactment" (OMR; see Figure 1). …”
Section: How Do Apes Ape?mentioning
confidence: 99%
“…Thus, observers may learn what change in the environment is needed for reward to be obtained. This form of nonimitative learning has been referred to as the emulation of affordances (Tomasello, 1996) or as object movement reenactment (Custance, Whiten, & Fredman, 1999). To control for this kind of learning, we included observers that were exposed to demonstrators that had been trained to stand away from the screen while it was being moved to the left or the right side unobtrusively by the experimenter.…”
mentioning
confidence: 99%